The incidence, risk and functional outcomes of intracranial haemorrhage in children with inherited bleeding disorders at one haemophilia center. (19th May 2016) - Bladen, M.; Main, E.; Khair, K.; Hubert, N.; Koutoumanou, E.; Liesner, R.
Abstract : Introduction: Intracranial haemorrhage (ICH) is the most serious bleeding event for patients with inherited bleeding disorders (IBD). The risks and long‐term consequences remain unknown. Aim: This single‐centre service evaluation aimed to identify the incidence, risks and long‐term outcomes following ICH in patients with IBD. Methods: The IBD database and medical notes between 1987 and 2013 were reviewed. Children without apparent neurological deficit following ICH completed standardized assessments and supplementary information sheets. Results: ICH was confirmed in 38/1111 children with IBD. The overall risk of ICH amongst children with IBD was 3.4% (95% CI: 2.5, 4.7%). However, 27/38 had an ICH in the first year of life, 18 of which were in the neonatal period. In children with IBD who had an ICH, the risks of ICH in the neonatal period or first year of life were 18/38 (47%) (95% CI: 32, 63%) and 27/38 (71%) (95% CI: 55, 83%) respectively. Mortality risk from ICH in children with an IBD was 5/38 (13%) (95% CI: 5.8, 27.3 %). Ten of 32 survivors had known neurological sequelae including motor disorder deficits (MDD) while 22 had no documented evidence of neurological impairment or MDD. Re‐evaluation was possible in 17/22 children, 8 of whom demonstrated evidence of MDD. After re‐evaluation, the risk of significant neurological MDD from ICH increased from 31% CI (95% CI: 18, 49%) to 56% CI (95% CI: 39, 72%). Conclusion: Risks and consequences of ICH in IBD were highest within the neonatal period and first year of life. MDD after ICH was not reliably identified in early life and ongoing monitoring in the first decade of life will facilitate educational support or physical rehabilitation.